New role of the antidepressant imipramine as a Fascin1 inhibitor in colorectal cancer cells - Alburquerque-González, Begoña; Bernabé-García, Manuel; Montoro-García, Silvia; Bernabé-García, Ángel; Rodrigues, Priscila Campioni; Ruiz Sanz, Javier; López-Calderón, Fernando F.; Luque, Irene; Nicolas, Francisco José; Cayuela, María Luisa; Salo, Tuula; Pérez-Sánchez, Horacio; et al. (Experimental & molecular medicine, 2020)
Serrated adenocarcinoma (SAC) is more invasive, has worse outcomes than conventional colorectal carcinoma (CRC), and is characterized by frequent resistance to anti-epidermal growth factor receptor (EGFR) and overexpression of fascin1, a key protein in actin bundling that plays a causative role in tumor invasion and is overexpressed in different cancer types with poor prognosis. In silico screening of 9591 compounds, including 2037 approved by the Food and Drug Administration (FDA), was performed, and selected compounds were analyzed for their fascin1 binding affinity by differential scanning fluorescence. The results were compared with migrastatin as a typical fascin1 inhibitor. In silico screening and differential scanning fluorescence yielded the FDA-approved antidepressant imipramine as the most evident potential fascin1 blocker. Biophysical and different in vitro actin-bundling assays confirm this activity. Subsequent assays investigating lamellipodia formation and migration and invasion of colorectal cancer cells in vitro using 3D human tissue demonstrated anti-fascin1 and anti-invasive activities of imipramine. Furthermore, expression profiling suggests the activity of imipramine on the actin cytoskeleton. Moreover, in vivo studies using a zebrafish invasion model showed that imipramine is tolerated, its anti-invasive and antimetastatic activities are dose-dependent, and it is associated with both constitutive and induced fascin1 expression. This is the first study that demonstrates an antitumoral role of imipramine as a fascin1 inhibitor and constitutes a foundation for a molecular targeted therapy for SAC and other fascin1-overexpressing tumors. Colorectal cancer: Antitumor antidepressant The antidepressant drug imipramine can block the activity of a protein that contributes to the progression of certain aggressive tumors. Serrated adenocarcinoma (SAC) is a form of colorectal cancer with a poor prognosis. A key factor in SAC development is the overexpression of the protein fascin1, which promotes the formation of structures that help cancer cells move around, thereby leading to metastasis. Pablo Conesa-Zamora at Santa Lucia University Hospital in Cartagena, Horacio Pérez-Sánchez at the Universidad Católica de Murcia in Guadalupe, Spain, and coworkers demonstrated that imipramine shows promise in binding to fascin1 and blocking its activity. The team analyzed over 9500 compounds as potential fascin1 blockers, identifying imipramine as a possible option. In tests on human tissues and in vivo studies using zebrafish, the drug reduced cancer invasion and metastasis.